Weather Influences Multiple Components of Greater Prairie‐Chicken Reproduction. Issue 1 (23rd September 2020) - Londe, David W.; Elmore, R. Dwayne; Davis, Craig A.; Fuhlendorf, Samuel D.; Hovick, Torre J.; Luttbeg, Barney; Rutledge, Jimmy
ABSTRACT: The influence of weather on wildlife populations has been documented for many species; however, much of the current literature has focused on the effects of weather within a season and consists of short‐term studies. The use of long‐term datasets that cover a variety of environmental conditions will be essential for assessing possible carry‐over effects of weather experienced in one season on behavior and fitness in subsequent seasons. In this study, we evaluated the effects of weather variables measured over multiple temporal scales on the reproductive performance and behavior of greater prairie‐chickens ( Tympanuchus cupido ) in Osage County, Oklahoma, USA, from 2011–2019. Considering weather over a range of temporal extents allowed us to determine the relative importance of short‐term weather events, such as daily temperature and precipitation, versus more chronic shifts in weather such as persistent drought on the reproductive performance of greater prairie‐chickens. We used an information‐theoretic model building approach to develop models describing the effects of daily weather variables and drought conditions on daily nest survival, nest incubation start dates, and clutch size. Daily nest survival was primarily influenced by conditions experienced during incubation with daily nest success declining in years with wetter than average springs and during extreme precipitation events. Daily nest survival also declined under higher maximum daily temperatures, especially in years with below‐average rainfall. Greater prairie‐chickens began nesting earlier and had smaller clutch sizes for initial nests and renests in years with warmer temperatures prior to the nesting season. Additionally, incubation of nests started later in drought years, indicating carry‐over effects in greater prairie‐chicken reproductive behaviors. Our work shows that if the weather in the Great Plains becomes more variable, with increasing frequency of drought and extreme precipitation events, wildlife species that inhabit these grassland landscapes will likely experience changes in reproduction, potentially influencing future populations. © 2020 The Wildlife Society. Abstract : Female greater prairie‐chickens experience reduced reproductive output due to extreme weather conditions in the Southern Great Plains, USA. In particular, daily nest survival declined in years with above average rainfall during the nesting season and on days that experienced extreme rainfall events. Further, warmer spring temperatures resulted in earlier nest initiation dates, smaller clutch sizes, and reduced daily nest survival.